Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Pancasila di SMP PGRI 1 Ciputat - Lestari, Dina; Rustandi, Roni (Universitas Al-Qolam Malang, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students' learning outcomes in the subject of Pancasila Education at SMP PGRI 1 Ciputat. The research employed a quantitative approach with a quasi-experimental design, involving two classes: an experimental class that applied the PBL model and a control class that used conventional teaching methods. The research instrument consisted of pretest and posttest questions, which were tested for validity and reliability, resulting in a Cronbach’s Alpha value of 0.745. The findings indicated a significant increase in the posttest scores of the experimental class from 52 to 75.84, while the control class improved from 48 to 67.12. The t-test showed a significant difference between the two groups. It can be concluded that the PBL model has a positive effect on improving students’ learning outcomes.